Potential of Cookies Coobisang with Biscuits “Milna" on The Increasing Weight of Babies Aged 6-9 Months - Sari, Novita; Wijayanti, Krisdiana; -, Arwani (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Background: Complementary food for ASI (MP-ASI) is additional food given to babies after they are 6 months to 24 months old. Providing MP-ASI aims to increase the energy and nutrients needed for babies because breast milk cannot meet the needs of babies along with increasing age and weight.Objective:Proving the comparative effect of Coobisang Cookies consumption combined with Ambon banana flour (Musa Paradisiaca) and purple sweet potato flour (Ipomea batatas L) with "Milna" Biscuits on weight gain in infants aged 6-9 months.Method: This type of research is True Experimental with the Two Group Pretest and Posttest Design. The independent variables were Coobisang Cookies and "Milna" Biscuits given for 30 days with 2 Coobisang Cookies weighing 24 g/piece and "Milna" Biscuits weighing 22 g/piece. The number of samples in this study were 36 infants aged 6-9 months divided into 2 groups, 18 intervention groups and 18 comparison groups.Results: The effect of the combination of Coobisang Cookies and "Milna" Biscuits for increasing baby weight 6-9 months obtained a p-value of 0.001 0.05. The average difference in the comparison of Coobisang Cookies (8455 grams) was higher compared to "Milna" Biscuits (8427 grams) and the increase in the Coobisang Cookies group first occurred in the second week, while in the "Milna" Biscuits group there was only an increase in the third week. Conclusion: Giving Coobisang Cookies can increase the weight of babies aged 6-9 months. Giving Coobisang Cookies can be an alternative based on the difference in weight between complementary foods in the comparison group. The basic ingredients for Coobisang Cookies are also easy to obtain and also economical.